A Retrospective Study of Chinese Patients With Giant Cell Arteritis (GCA): Clinical Features and Factors Associated With Severe Ischemic Manifestations. Issue 13 (March 2016) - Sun, Fei; Ma, Sha; Zheng, Wenjie; Tian, Xinping; Zeng, Xiaofeng
Abstract : Abstract: A retrospective study was performed on 70 giant cell arteritis (GCA) patients in Peking Union Medical College Hospital (PUMCH). The aim of this study was to describe the clinical features of these Chinese GCA patients and explore the possible associated factors for severe ischemic manifestations. Medical charts of all patients were reviewed, and the demographic, clinical, and laboratory data were analyzed. The mean age at disease onset was 65.2 years old, and the ratio of male to female was 1:1. Fever and headache were most prominent symptoms at onset, which occurred in 51.4% and 30.0% of patients, respectively. Common manifestations at diagnosis were constitutional symptoms (85.7%), headache (68.8%), visual impairment (38.6%), jaw claudication (30%), scalp tenderness (30%), and concurrent polymyalgia rheumatic (27.1%). No significant difference in clinical manifestations between genders was observed. Comparisons between patients with and without severe ischemic manifestations including jaw claudication, permanent visual loss, or cerebrovascular accident had shown that fever and asthenia were significantly less frequent in patients with severe ischemic manifestations ( P = 0.006 and 0.023, respectively), and the mean value of erythrocyte sedimentation rate (ESR) was significantly lower in patients with severe ischemic manifestations than patients without ( P = 0.001). History of smoking was more frequent in patients with severe ischemic manifestations ( P = 0.038). This is the largest group of GCA patients from China so far. When compared our data with patients reported in the literature, this series of GCA patients were younger and without female predominance. The clinical manifestations of patients in this report were similar to other studies except for a higher prevalence of constitutional symptoms. The results of this study indicated that lower systemic inflammatory response and the history of smoking might be associated with severe ischemic damages.